The Influence Of Vendor Performance Evaluation, Product Quality, And Price On User Satisfaction Of Laboratories Within Universitas Pertamina - Erick Ivan Gian; Heni Iswati (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the influence of vendor performance evaluation, product quality, and price on user satisfaction of laboratory facilities at Universitas Pertamina. A quantitative research approach was employed, and data were collected through a structured questionnaire distributed to 65 respondents, utilizing a total sampling method. The research variables were measured using a five-point Likert scale and analyzed through multiple linear regression with the assistance of SPSS 22.0. The findings reveal that vendor performance, product quality, and price each have a positive and significant partial effect on user satisfaction. Furthermore, all three variables simultaneously exert a significant influence on user satisfaction. The results emphasize the critical role of maintaining high vendor standards, ensuring the quality of products and services, and implementing competitive pricing strategies to enhance user satisfaction in laboratory environments. These insights offer valuable implications for laboratory management practices in higher education institutions.